PMMK. : Kunstmap PMMK. (Oostende : PMMK (Provinciaal Museum voor Moderne Kunst), 1975)
Bogart, Bram ; Brusselmans, Jean ; De Clerck, A. ; De Smet, Gust ; Duchateau, H. ; Gentils, Vic ; Joostens, Paul ; Mortier, Anton ; Servranckx, Victor ; Tytgat, Edgar ; Verheyen, Jef ; Wierusz-Kowalski, T.
Nederlands
boek